(untitled) (CIPEEX, 2025)
Cardiovascular diseases are considered the leading cause of mortality worldwide, and maintaining optimal cardiovascular health significantly contributes to reducing risk factors, including anthropometric measurements associated with obesity. The objective of this study is to compare CVS with anthropometric markers related to obesity among university staff at a higher education institution. This is a cross-sectional study conducted with 121 university staff of both sexes (71 women and 50 men). Seven metrics assessed CVS: diet, physical activity level, smoking status, total cholesterol, fasting blood glucose, systemic blood pressure, and body mass index. The anthropometric measurements considered were waist circumference (WC) and waist-to-hip ratio (WHR). The project was approved by the UniEVANGÉLICA Research Ethics Committee under number 4.512.382/2021. Data normality was tested using the Kolmogorov-Smirnov test. For comparison between groups, independent-samples ANOVA and the Kruskal-Wallis test were performed. The group with ideal CVS had lower WC (p<0.001) and WHR (p<0.001) values compared to the groups with moderate and poor CVS. It is concluded that ideal CVS levels are associated with better anthropometric indicators related to obesity, highlighting the importance of cardiovascular health promotion strategies for reducing the risk of cardiovascular disease.